Passive fit and time efficiency for prefabricated versus conventionally constructed cobalt chromium CAD\CAM 3-unit implant supported frameworks in free end saddle models: a pilot invitro study - Mohamed El-Sayed Kamel; AlHassan Alaa Eldin Alsayed; Mohamed Amr ElKhashab; Nancy Nader; Iman AbdelWahab Radi (BMC, 2024)
Abstract Background The passive fit of 3-unit implant supported prefabricated metal screw-retained prosthesis before implant placement might be difficult. Hence, we aim to evaluate the passive fit and time efficiency of CAD/CAM 3-unit implant supported fixed prostheses that were constructed based on virtual versus those based on actual implant positions in Kennedy Class I models. Methods A sample of 5 Kennedy class I models with thin wiry ridges were restored by 20 frameworks bilaterally, 10 based on actual (group A) and 10 based on virtual (group V) implant positions. The models were imaged using cone beam computed tomography and scanned using an intraoral scanner. The STL (Standard Tessellation Language files) and the DICOM (Digital Imaging and Communications in Medicine) files were registered on a 3D planning software. A CAD/CAM surgical guide was planned, resin printed and used for installing 6 implants bilaterally. In group V, the framework was designed based on the virtual scan bodies and virtual multi-unit abutments, while in group A intra-oral scanning of the model after attaching the scan bodies was necessary. Frameworks of both groups were milled and tested for passive fit using 8 clinical tests. McNemar and Wilcoxon signed rank tests were used to study the effect of the group on passive fit and time efficiency, respectively. The significance level was set at P ≤ 0.05. Results No statistically significant difference was found between group V and group A frameworks regarding passive fit (p-value = 1, OR = 0.5) and time efficiency (P = 0.179, Effect size = 0.948). Conclusion Within the limitations of this study, it can be concluded that in free end saddle cases, prefabricated CAD\CAM 3-unit implant-supported cobalt chromium screw retained prostheses can achieve an adequate passive fit. However, their fit might be negatively affected in thin ridges and they might require some adjustments.